A geographic view of expansion choices by U.S. firms in China. Issue 1 (1st January 2016) - Wooster, Rossitza B.; Banis, David; Khalid, Ayesha
Abstract: How does geography matter for explaining the location patterns of U.S. companies in China? We combine insights from the literature on economic geography and spatial interdependence in foreign direct investment (FDI) activity to provide a comparative analysis using both sectoral regression results and maps that illustrate patterns in the data. We use a unique sample of publicly traded U.S. firms that announced expansion of operations into China between 1980 and 2005. Regression results show that, relative to the tertiary sector, firm characteristics matter more for primary sector firms, whereas province characteristics matter more for secondary sector firms. Additionally, our GIS analysis reveals a high level of locational concentration and differences in provincial characteristics over time. Overall, we find that combining GIS methods with FDI data can provide a richer picture of economic activity that is highly accessible to both academics and practitioners.